INTERNALISASI NILAI-NILAI PERJUANGAN MAULANA SYEIKH MUHAMMAD ZAINUDDIN ABDUL MADJID MELALUI WISATA MAKAM - Herman Supriadi; Irwan Rahadi; Muh. Hilmi Pauzi; Taufik Kurniawan; Ramli Hidir (Fakultas Pariwisata Universitas Pancasila, 2022)
Establishing a particular tomb has many purposes, one of which is to remember the life story of the copse. The focus of this research is the tomb of a national hero and a religious leader on the island of Lombok, namely Maulana Sheikh Muhammad Zainuddin Abdul Majdid. His grave was visited by many pilgrims from various regions in Indonesia. From the questionnaires distributed to visitors, 101 respondents were found. From the tabulated data, it was found that the purpose of the visitors to Maulana Sheikh Muhammad Zainuddin Abdul Madjid's grave was classified into three parts. One of these three groups is visiting the grave because they want to remember and pay attention to the next generation about his struggles (81.89%) the remaining visitors around 8.9% (respondents) visit only to walk and follow the orders of their parents and the remaining about 2 people or 2.2% to keep the vow or promise they ever sought. Thus, from the results of this study, we can conclude that visiting the grave of Maulana Sheikh Muhammad Zainuddin Abdul Madjid can be a medium to introduce him and his struggle to generations after him, how he fought to defend Religion, Nation and State so that the next generation can be free from struggle.